تقويم كفاءة التسويق السياحي في سورية - برهوم أديب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يمكننا القول أن السياحة هي صناعة المستقبل, ولذلك فهي حاجة ٌ أساسية ٌ لتقدم سورية وتنميتها في القرن الحالي. وبما أن سورية تتمتع بالكثير من الإمكانيات والمقومات التي تمكنها من منافسة العديد من البلدان الأخرى في جذب السياح ، فإننا نرى أن التسويق السياحي يلعب دورا ًمهما ًفي إبراز هذه المقومات. لهذا ارتأينا اتخاذ موضوع تقويم كفاءة التسويق السياحي كمحور ٍ لدراستنا من خلال التركيز على جوانب هامة ٍمنها: إجراء دراسة تحليلية لواقع العرض والطلب السياحيين في سورية وإبراز المشاكل القائمة ، واستخلاص مجموعة من النتائج والمقترحات التي تساعد على تحسين واقع التسويق السياحي في سورية. We can say that tourism is the future industry so it is an essential necessity for the development and progress of Syria. Since Syria possesses a lot of abilities and components that enable it to compete with many other countries in attracting tourists , whereas tourist marketing performs a distinguished function in featuring these components. Therefore, the study treats the notion of evaluating the efficiency of tourist marketing as an axis for it through concentrating on some important aspects such as carrying out an analytical study of the present situation of tourist supply and demand demonstrating the troubles they suffer, and concluding a set of results and suggestions that may help in improving the situation of tourist marketing in Syria. Some of the results reached by this study are: 1- The contribution of tourism in the national income is still below what is required. 2- There is a steady decrease in the number of hotel residents when compared with the number of visitors. 3- The tourism in Syria is still seasonal. 4- There is not sufficient interests in tourist marketing in general, and in tourist promotion in particular.